Konstruksi Sintaksis Kaifiatul Ikhbar dalam Akad Ijab Kabul Pernikahan - Muchlish Huda, Muhammad; Arifin, Samsul; Ma’arif, Miftakhul (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2020)
In the context of composing Arabic sentences, the rules of kaifiatul ikhbar are included in the rules which are basic and foundation. The kaifiatul ikhbar rules are formed from the composition of the mubtada and khobar and are used in various forms of sentences, including the sentence structure of the marriage consent. Accuracy in pronouncing the kabul marriage license sentence including the arrangement of the preacher and khobar becomes important considering this kabul consent will be a legal requirement or cancellation of a marriage contract. This study attempts to analyze and present several forms of kabul mariage agreement and syntactic analysis, especially in the kaida of kaifiatul ikhbar. By using a library approach and linguistic analysis from its syntactic aspects, the results of this study indicate that there are 11 forms of kaifiyatul ikhbar with various syntactic analysis specifications. This shows that the form of kaifiatul ikhbar in the marriage contract is actually not only one forms, but with a variety of sentence forms